2022
DOI: 10.1002/pds.5538
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating awareness, knowledge and practice of healthcare professionals following implementation of a revised pregnancy prevention programme for isotretinoin in Ireland: A multi‐stakeholder cross‐sectional study

Abstract: Purpose: In 2018, following an EU-wide safety review, a revised pregnancy prevention programme (PPP) was introduced for isotretinoin (Roaccutane ® ). This study aimed to examine awareness, knowledge, and experience implementing the revised isotretinoin PPP in clinical practice across three healthcare professional (HCP) groups in Ireland.Methods: A cross-sectional study using anonymous online surveys among general practitioners (GPs), community pharmacists, and specialist consultants was undertaken. Descriptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Following the implementation of the revised isotretinoin PPP, the awareness, knowledge, and experience of implementing the PPP in clinical practice has been studied in Ireland. Hughes et al [ 10 ] showed that healthcare professionals were highly aware (≥ 87%) that isotretinoin should not be prescribed to women of childbearing age unless PPP conditions are met. However, the implementation of this knowledge varied greatly in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the implementation of the revised isotretinoin PPP, the awareness, knowledge, and experience of implementing the PPP in clinical practice has been studied in Ireland. Hughes et al [ 10 ] showed that healthcare professionals were highly aware (≥ 87%) that isotretinoin should not be prescribed to women of childbearing age unless PPP conditions are met. However, the implementation of this knowledge varied greatly in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, 47.6% of specialists provided patients with a reminder card when initiating the treatment, while only 11.8% of general practitioners did the same. Only 26.1% of community pharmacists provided patients with a reminder card at each dispensing [ 10 ]. It is questionable whether sending hard copies or emailing safety information to physicians is an efficient way to implement risk minimization measures in daily practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies in the Netherlands, Belgium, and France found that 81.8 %, 43.1 %, and 60 % of pharmacists, were aware of this fact, respectively [ 31 , 35 ]. In Ireland, 39.5 % of healthcare professionals, including pharmacists limited isotretinoin prescriptions to 30 days to support regular follow‐up [ 36 ]. The implementation of an isotretinoin dispensing education program in these countries could explain the gap in awareness about isotretinoin dispensing practices when compared with Jordan.…”
Section: Discussionmentioning
confidence: 99%